1995
DOI: 10.3189/s0260305500015718
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase in South Pole snow accumulation

Abstract: This paper summarizes the 37 year history of net accumulation measurements at the geographic South Pole obtained by numerous investigators using a variety of techniques. These data lead to the conclusion that annual net snow accumulation has increased in the vicinity of South Pole Station (SPS) since 1955. The records were examined for evidence of a “station effect” and it is concluded that not all of the observed increase can be attributed to snow drift associated with the presence of the station. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
5
29
0
Order By: Relevance
“… Pourchet et al [1983] observed a general increase of 30% in the accumulation at 14 Antarctic sites (including Vostok, Dome C, South Pole, and Ross Ice Shelf) in the period 1960–1975. This general trend was also observed some years later in the South Pole area, with an increase of 32% between 1960 and 1990 [ Mosley‐Thompson et al , 1995]. In Wilkes Land, Goodwin [1991] and Morgan et al [1991] found a decrease in accumulation rate from 1955 to 1960, with an increase during the following period.…”
Section: Accumulation Rate Records and Distributionsupporting
confidence: 52%
“… Pourchet et al [1983] observed a general increase of 30% in the accumulation at 14 Antarctic sites (including Vostok, Dome C, South Pole, and Ross Ice Shelf) in the period 1960–1975. This general trend was also observed some years later in the South Pole area, with an increase of 32% between 1960 and 1990 [ Mosley‐Thompson et al , 1995]. In Wilkes Land, Goodwin [1991] and Morgan et al [1991] found a decrease in accumulation rate from 1955 to 1960, with an increase during the following period.…”
Section: Accumulation Rate Records and Distributionsupporting
confidence: 52%
“…The recent increase of accumulation rate and δ 18 O are within the range and rate of change of previous variations. However, the increasing accumulation rate over the last 100 years seems to be the most consistent climatic signal from the Weddell Sea region, as it is also found in studies from the Antarctic Peninsula (Thompson and others, 1994) and also at South Pole (Mosley-Thompson and others, 1995).…”
Section: Discussionsupporting
confidence: 75%
“…enhancement during the period AD 1800–50. There is also an increase during the 20th century, as also seen throughout the Antarctic Peninsula and at South Pole (Thompson and others, 1994; Mosley-Thompson and others, 1995). No clear relationship is seen between δ 18 O and the annual accumulation, underlining the complicated meteorological situation of the Weddell Sea and Antarctic Peninsula region.…”
Section: Resultsmentioning
confidence: 89%
“…These include analysis of ice-core data by Morgan et al (1991), observations of snow accumulation at the South Pole from 1955 to 1992 by Mosley- Thompson et al (1995), and studies based on atmospheric model analysis. Cullather et al (1998) calculated Antarctic net precipitation from ECMWF operational analysis and precipitation from National Centers for Environmental Prediction (NCEP) reanalysis for 1985-1995, and found a positive trend of +2.0 to +2.5 mm yr −2 (our result for the same period for ERA-40 net precipitation is −0.20 mm yr −2 , but the trend is not statistically significant).…”
Section: Precipitation and Evaporationmentioning
confidence: 99%